Otomatisasi Pemberkasan Arsip Aktif Elektronik Pada Aplikasi Layanan Administrasi Mahasiswa - Fathurrohman, Fathurrohman (Perpustakaan dan Arsip Universitas Gadjah Mada, 2024)
Business information systems, namely electronic-based service applications usually don't automatically provide active archive filing features for electronic records generated from the business information system. Electronic Records are information contained in electronic files and media, which are created, received, or maintained by organizations or individuals and store them as evidence of activities. Like conventional records, electronic records that are created must be filed systematically and logically according to the context of their activities so that they become one file that has information relationships, similar types or similar problems. Student academic administration services at FMIPA IPB produce